Effects of Nationwide Lockdown due to COVID-19 on Ambient Air Quality in the State of West Bengal, India - Ghosh, B.; Nayek, S.; Padhy, P. K. (Journal of Scientific Research, 2023)
The present study assessed the nationwide lockdown impacts on the air pollution situation across West Bengal, India. Air pollution data was collected from the online monitoring stations of the Central Pollution Control Board across West Bengal. The gradual declining pattern of overall pollution status was observed during the lockdown phase from the pre-lockdown phase. The early unlocking stage found slow and gradual increasing air pollution levels. Siliguri’s pre-lockdown ‘poor’ Air Quality Index (AQI) improved in the lockdown phase to ‘satisfactory’ level. ‘Moderate’ level AQI in Asansol of the pre-lockdown stage improved to ‘satisfactory’ level during the lockdown phase. Pre-lockdown AQI of both Kolkata and Howrah changed from ‘moderate’ to ‘good’ level during the lockdown phase. Unlike other pollutants, the ozone level increased in Kolkata, Howrah, and Siliguri in the lockdown phase. The early monsoonal washout possibly caused the changes in the pattern of pollution status of specified periods in the 2019 and 2020. Thus, in the study period of lockdown in 2020, the decrease in pollution level may not only caused by the stoppage of vehicles or industry but also have a possible natural influence.